Turnover Intention among Employees of Small and Medium Enterprises (SMEs): The Moderating Role of Employee Engagement - Siti Zulaikha Wulandari; Eka Pariyanti; Febriyanto Febriyanto (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This study was conducted to ascertain the influence of person-organization fit (P-O fit) and job satisfaction on turnover intention within Small and Medium Enterprises (SMEs). Moreover, the mediating role of employee engagement in both of these associations was explored.  Methodology – A cross-sectional survey was administered, targeting Small and Medium Enterprises (SMEs) in Lampung, Indonesia. The study involved 198 participants and data collection was conducted through the utilization of a questionnaire. To test the hypotheses, a quantitative approach incorporating structural equation modeling (SEM) was employed, using the AMOS software package version 24.0. Findings – The study showed that P-O Fit and job satisfaction had a negative impact on turnover intention. Employee engagement was also identified as a mediating factor in both of these relationships. Originality – There was a lack of extensive study examining the correlation between the variables within the specific context of SMEs, particularly in Lampung. Therefore, this study was carried out to introduce a study model grounded in social exchange theory.